Versuch einer textlinguistischen Analyse ausgewählter deutschsprachiger Testamente des Königlich Preußischen Adels aus dem 17. Jahrhundert - Owsiński, Piotr A.; Paluch, Anna (Acta Neophilologica, 2021)
This article presents an attempt to show the specific features of the German legal language in the chosen wills of the nobility from Royal Prussia of the 17th century, in the area of German settlement in the East. The investigation aims to answer the question as to whether the examined testaments suit the pattern of the will as a text type. The author focuses on the graphemic, lexical and syntactic levels of the testament. The outline of structure and function of wills provides the background for such a defined research area.